2010
DOI: 10.1179/016164110x12556180206158
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing optic nerve crushes with an aneurysm clip

Abstract: The present findings suggest that Yasargil aneurysm clip effectively produces permanent injury to the optic nerve with evidence from retrograde tracing of RGCs and may provide a standard technique for optic nerve crush studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…In experimental animal studies, ON crush provides a reliable method for studying quantitative anatomical effects on novel neuroprotection or neurodegeneration after insults [23,27,28,29,30]. Our results demonstrate that a complete block of axoplasmal flow was caused by the jewel forceps for 15 s. The jewel forceps has been used in other experiments of ON crush [21,22].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In experimental animal studies, ON crush provides a reliable method for studying quantitative anatomical effects on novel neuroprotection or neurodegeneration after insults [23,27,28,29,30]. Our results demonstrate that a complete block of axoplasmal flow was caused by the jewel forceps for 15 s. The jewel forceps has been used in other experiments of ON crush [21,22].…”
Section: Discussionsupporting
confidence: 49%
“…With crush duration shorter than 30 s with a microvascular clip, the FG flow was well preserved. Other reports also demonstrated that various pressures exerted by a clip and different crush durations could result in a different optic nerve damage [18,23,31]. In sum, our results indicate that different instruments to induce crush injuries with variable durations may influence the efficiency of retrograde labeling.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The optic nerve crush was performed as described previously (Feng et al, 2010). In brief, a lateral canthotomy was made in the superior orbital rim, and an incision of the conjunctiva was performed lateral to the cornea.…”
Section: Methodsmentioning
confidence: 99%
“…Degeneration occurs in a swelling in the affected nerve fibers as a result of compression of nerve tissue. In 2010 Feng Dong-Fu [5] suggested to damage the optic nerve by compressing it with aneurisms clips and showed retrograde death of retinal ganglion cells. Thus, the morphological manifestations of lesions of the proximal and distal parts of the ipsilateral and opposite side of visual pathway are still not fully understood and therefore require clarification.…”
Section: Introductionmentioning
confidence: 99%